Engineering mechanics : dynamics - Pytel, Andrew. (Brooks/Cole, 1999)
This book is about: Dynamics of a Particle; Work-Energy and Impulse-Momentum principles for a particle; Dynamics of particle systems; Planar kinematics of rigid bodies; ...